Analysis of the Implementation of Community-Based Tourism (CBT) Principles in the Development of Sreseh Mangrove Tourism (WMS) in Sampang Regency - Rinni Yuriaty; Sri Roekminiati; Dandy Patrija Wirawan; Zainal Fatah (Educational Dynamics: International Journal of Education and Social Sciences, 2026)
Community-Based Tourism (CBT) development aims to improve community welfare through active participation, equitable distribution of economic benefits, environmental and socio-cultural conservation, institutional strengthening, and destination sustainability. This study aims to analyze the implementation of CBT principles in the development of Sreseh Mangrove Tourism in Sampang Regency. The study employed a qualitative method with a descriptive approach. Data were collected through observation, interviews, and documentation and were then analyzed using the interactive model of Miles, Huberman, and Saldaña. The findings show that CBT principles have been implemented through community involvement in tourism management, the creation of economic opportunities, inter-institutional collaboration, mangrove conservation, and the preservation of local traditions and wisdom. However, implementation has not yet been optimal because community participation in decision-making remains limited, economic benefits have not been distributed evenly, institutional capacity needs to be strengthened, and challenges remain in accessibility, supporting facilities, promotion, tourism product development, and human resource capacity. Therefore, stronger collaboration among stakeholders, enhanced community capacity, and more inclusive destination management are required to support the sustainable implementation of CBT.